Disabling seclusion: an integrated job empowerment and skills development centre for persons with intellectual disabilities - Walele, Malika (My University, 2016)
People with intellectual disabilities are considered to be marginalised in our society. They continue to face prejudices, stigmas and are discriminated against resulting in social exclusion. This thesis develops a framework and methodology for pursuing inclusive environments and viable productivity within the workplace for persons with intellectual disabilities. The lack of opportunities within the workplace for individuals with intellectual disabilities intensi es their exclusion from society. The road to achieving inclusivity within the workplace has become a challenging one to navigate, as previous strategies which were developed to enable equality are far removed from what was intended. More often than ever before, employers are challenged from both a legal and political perspective for failing to diversify the workplace. Equality advocates as well as those who attempt to diversify their companies face obstacles within the workplace, namely inadequate resources or uncertainty about their appropriate role or approach in dealing with minorities. The building will serve as a learning hub, used by both persons with intellectual disabilities and people who are commonly referred to as able bodied. It will function as a level between education (if any) and the period before entering the workplace. The learning hub will afford persons with intellectual disabilities the opportunity to explore their capabilities in environments similar to that of a workplace and gain knowledge and experience prior to entering the workplace. The program envisaged in this thesis will demonstrate that this intervention is mutually bene cial to a company and the individual with an intellectual disability. In the first instance, the employer acquires knowledge and skills to act as a catalyst in enabling the transition of a person with an intellectual disability into the workplace to augment inclusivity. Secondly, the person with an intellectual disability through the program will be clothed with knowledge and expertise enabling meaningful participation amongst able-bodied employees. The transformation within workplaces as a result of the knowledge gained through this centre should create an enabling environment that incorporates the individual’s needs or one that best satis es their needs. The support by the employer is vital in the outcome and success of integrating people with disabilities into the social framework. The building is developed around a range of interactive programs between those with intellectual disabilities and people acting as the supervisors from workplaces. The supervisors, through training will be best placed to oversee progression and be empathetic toward staff with intellectual disabilities. This will enable them to transfer their knowledge and expertise of dealing with and accommodating employees with intellectual disabilities to their respective workplaces. A mock work environment will form the basis of the experiential training ground and in conjunction with job sampling will establish where a user will be best suited within the work environment. Public facilities encourage members of the public to become active participants within the space providing exposure and understanding towards those with intellectual disabilities. The centre is expected to be both accessible and lasting and will mediate experiential training and aligning it to workplace practices. The centre will be a vital space to enhance inclusion and for producing sustainable change for this marginalised group of persons. The building is located within an educational precinct on Melle Street, Braamfontein. The site which is in close proximity to the Central Business District allows for the centre to feed into businesses and vice versa. The location also allows for easy access to people from all over Johannesburg utilising various transport methods. The site being amid universities and schools ensures integration and optimum use, for educational facilities to link into this program. It also allows for social cohesion through exposure between the users of the building and other students in the surrounding area.
This document is submitted in partial fullfilment for the degree: Master of Architecture [Professional] at the University of the Witwatersrand, Johannesburg, South Africa, in the year 2015.
Keywords: People with mental disabilities--Institutional care--South Africa; Mental retardation facilities--South Africa; Community development--South Africa--Johannesburg